Integrative taxonomic approach to the cryptic diversity of Diplostomum spp. in lymnaeid snails from Europe with a focus on the 'Diplostomum mergi' species complex - Selbach, Christian; Soldánová, Miroslava; Georgieva, Simona; Kostadinova, Aneta; Sures, Bernd (Parasites & vectors, 2015)
BACKGROUND: Recent molecular studies have discovered substantial unrecognised diversity within the genus Diplostomum in fish populations in Europe and North America including three species complexes. However, data from the first intermediate host populations are virtually lacking. This study addresses the application of an integrative taxonomic approach to the cryptic species diversity of Diplostomum spp. in natural lymnaeid snail populations in Europe with a focus on the 'D. mergi' species complex. METHODS: Totals of 1,909 Radix auricularia, 349 Radix peregra, 668 Stagnicola palustris and 245 Lymnaea stagnalis were sampled at five reservoirs of the Ruhr river system in Germany and screened for infections with Diplostomum spp. Cercariae were examined and identified alive, fixed and under scanning electron microscopy. Sequences from the barcode region of the cytochrome c oxidase subunit 1 (cox1) mitochondrial gene and from the internal transcribed spacer cluster (ITS1-5.8S-ITS2) of the rRNA gene were amplified for 51 and 13 isolates, respectively. RESULTS: Detailed morphological and molecular analyses provided evidence for three named species (Diplostomum spathaceum, D. pseudospathaceum and D. parviventosum), and a further four species-level lineages ('D. mergi Lineages 2-4' and 'Diplostomum sp. Clade Q' in the lymnaeid snail populations from the Ruhr river basin. The paper provides the first descriptions of molecularly identified cercariae of D. spathaceum and of the cercariae of D. parviventosum, three lineages of the 'D. mergi' species complex and of 'Diplostomum sp. Clade Q'. CONCLUSION: The integration of molecular and morphological evidence for Diplostomum spp. achieved in this study will serve as a baseline for species identification of these important parasites of snail and fish populations and thus advance further studies on the distribution of Diplostomum spp. in Europe.
Keywords: Molecular Sequence Data; Snails; Male; biodiverzita; Severní Amerika; mužské pohlaví; Trematode Infections; Německo; North America; hlemýždi; ženské pohlaví; zvířata; nemoci ryb; fylogeneze; Germany; Trematoda; Biodiversity; Fish Diseases; Fishes; molekulární sekvence - údaje; ryby; Female; Phylogeny; infekce červy třídy Trematoda; Animals